Scaling distributed training in rural primary care: a Philippine model for LMIC health systems - Riel-Espina, Aileen T.; Limpoco, Anna Guia Orejola; Lachica, Reggiena Las Piñas; Bolo Jr., Renato Banez; Lachica, Daniel John Dineros (Frontiers in Medicine, 2025)
Low- and middle-income countries (LMICs) continue to face persistent shortages of trained primary care providers in rural areas. This challenge is compounded by the lack of locally accessible residency training programs, which limits opportunities for physicians to develop the skills needed to serve these underserved communities. Consequently, physicians working in underserved municipalities leave their posts to pursue specialization, exacerbating the workforce shortage. In Sorsogon, a province in the Philippines, this gap is further compounded by the mismatch between existing training models being offered in urban hospitals with a curative, episodic-care orientation and the province’s need for a community-embedded program anchored on health promotion, disease prevention, and continuity of care. This community case study describes the design and implementation of the Sorsogon Province-wide Practice-Based Family and Community Residency Training Program (PBFCMRTP), a distributed, in-situ model co-developed by the Provincial Government of Sorsogon and the Philippine Academy of Family Physicians (PAFP). Grounded in the principles of the Universal Health Care (UHC) Law of the Philippines, the program enables rural physicians to undergo residency training while remaining in their practice sites—provincial and district hospitals, as well as rural health units—ensuring uninterrupted service delivery during training. Using a hybrid, spiral curriculum that combines digital learning classrooms, peer learning, integrated case discussions, periodic practice site visits, and workplace-based assessments, remote supervision with mentoring sessions by accredited family medicine trainers, the program emphasizes health systems integration, primary care leadership, and community-responsive care grounded on the Patient-Centered, Family-Focused, and Community-Oriented (PFC) approach. Over 4 years, the program has matured from a new program granted provisional accreditation status by the PAFP Residency Accreditation Board to full (Level 3) accreditation status. It has successfully prepared its trainees to lead primary care delivery in resource-constrained, community-based settings. This case highlights the feasibility of scaling practice-based residency training models in LMICs through strong local governance, policy support, and community-responsive curriculum design. Key enablers include the strategic use of digital platforms, trainees’ commitment, dedicated trainers, and intersectoral collaboration. Lessons from the Sorsogon experience may inform efforts to decentralize medical education and strengthen rural health systems in similar contexts.